Swimming coaches’ professional development and training practices: an international survey - Dalamitros, Athanasios A.; Nikolopoulos, Alexandros; Varsamidou, Katerina; Gourgoulis, Vassilios; Zafeiroudi, Aglaia; Loukovitis, Andreas; Clemente-Suárez, Vicente Javier; Tornero-Aguilera, José Francisco; Powell, Cormac (Frontiers in Sports and Active Living, 2023)
This study investigated swim coaches' perceptions of professional development issues and current training practices according to their coaching experience, education level, and gender. An online survey (January—April 2022) was completed by 123 swim coaches (96 male/27 female) of competitive swimmers based in 41 countries. The survey consisted of 36 questions divided into six sections: (1) background information, (2) developing swim coaching through learning, (3) self-evaluation, (4) interpersonal-intrapersonal interactions, (5) life skills, and (6) analyzing swimming performance. Pearson chi-square assessed the relationship between the frequency of responses and professional background and gender. The survey results indicated that swim coaches' educational level is potentially one of the most influential parameters affecting the coaches' perceptions about their own professional development. The data presented may be used for the future design of coach education programmes as they advance current knowledge on understanding psycho-social issues related to professional development and training perceptions involved in the competitive swimming environment.